PENGARUH MEDIA PEMBELAJARAN NEARPOD TERHADAP KEAKTIFAN BELAJAR PPKN SISWA KELAS IV SD NEGERI 209 KAJAOLALIDDONG KABUPATEN BONE - Mujahidah; Nurul Azizah Rahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the effect of the use of Nearpod learning media on the activeness of learning PPKn of fourth-grade students of SD Negeri 209 Kajaolaliddong, Bone Regency. The purpose of this study is to determine the level of student learning activeness before and after the use of Nearpod learning media, as well as to determine the effect of using the media on student learning activeness. The approach used in this study is a quantitative approach, with a pre-experimental research type and One Group Pretest-Posttest Design. The data source in this study was 25 fourth-grade students of SD Negeri 209 Kajaolaliddong. Data collection techniques were in the form of learning activeness questionnaires and observation sheets. Data analysis techniques used descriptive statistical analysis and inferential statistics through normality tests and Paired Sample t-Test tests. The results of this study indicate that: (a) Students' activeness in learning PPKn before the use of Nearpod learning media was in the medium category with an average value of 60, and after the use of Nearpod media increased to 80 which is in the high category; (b) There is a significant influence of the use of Nearpod learning media on student learning activity, as evidenced by a significance value of 0.000 < 0.05 and a t-count value of 16.361 > t-table 1.713872. Thus, it can be concluded that the use of Nearpod learning media has a significant positive effect on the learning activity of PPKn in grade IV students of SD Negeri 209 Kajaolaliddong, Bone Regency.